FOOD DELIVERY SERVICE: THE EFFECTS OF PERCEIVED QUALITY, PERCEIVED EASE OF USE AND PERCEIVED VALUE TOWARDS CUSTOMER SATISFACTION - Sperico Michael Alden; Nur Shuhadah Rosshahpudin; Siti Anis Adilah Tarmazi; Suria Sulaiman; Najua Mohd Ali, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Consumers and distributors have benefited from the food industry just as much as food producers have. Nowadays, an online food delivery system is essential due to recent advances in the industry and the increased internet usage. Understanding the key success factors that contribute to sustainable growth and profitability in this space is essential for businesses looking to succeed in this rapidly evolving market. While there are many benefits to ordering food online, there are also several issues that need to be addressed. The objective of this study is to determine the critical success factors of the online food delivery service towards customer satisfaction. Total of 306 people that have experienced using the online food delivery system were surveyed from January till May 2022, and questionnaire were analysed by using the SPSS. Findings show that perceived quality, perceived ease of use and perceived value have positive relationship towards customer satisfaction. It is seen as opportunities for service providers to reap the benefits of recurring earnings from consumers by providing fast delivery, good meals, and fair promotions.